Cutting, Reading, Re-Membering: Parade's End's Elliptical History …. Issue 2 (August 2021) - Dutton, James
Abstract : This essay reads Ford Madox Ford's Parade's End materially, to claim that Ford's radically 'modernist' style worked to refigure history on the basis of the literary mark. Ford's innovative use of the material elements of writing allows his readers to approach history as materialistic historio graph y – a key idea for Paul de Man – that reads writing as marks and traces independent of fluctuating ideological abstractions. In Parade's End, Ford's narration avoids extra-textual context-building, instead sticking as tightly (and often bewilderingly) as possible to the interiority of a character's consciousness. Notably, this technique interacts with the material world in a similar way to de Man's approach to reading. This allows Ford to stage the 'writing' of history, where trace-chains are constantly refigured as material inscriptions, taken up and made sense of anew. The essay first interprets Ford's attitude to history as a creative act, ironised by his protagonist Tietjens' belief in the certainty and self-evidence of unified historicism. It then describes the 'elliptical' structure of one of the novels' key scenes, where Tietjens is forced to learn the unfinishable nature of history–especially via written forms (like the ellipsis itself) that do not speak. Finally, it directs its attention to the tetralogy's conclusion, 'voiced' by a mute narrator, that inscribes the potential for meaning to always remain in an unpredictable future. This 'theotropic' force cuts through Ford's novels, and in doing so gestures to the ellipsis from which all reading has, always-already, been re-membered.